POTENTIAL OF KOMBUCHA COFFEE AS A FUNCTIONAL DRINK TO IMPROVE IMMUNITY AND MAINTAIN INTESTINAL MICROBIOTA BALANCE: LITERATURE REVIEW - Aini, Qurratu; Hanum, Ulia; Fadhila, Arif (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2025)
Functional beverages based on fermentation are increasingly in demand as public awareness of the importance of preventive health increases. Kombucha coffee, an innovation from coffee fermentation using bacterial and yeast cultures (Symbiotic Culture of Bacteria and Yeast or SCOBY), offers a combination of the benefits of coffee and traditional kombucha. This article examines the potential of kombucha coffee as a functional beverage that contributes to improving the immune system and maintaining the balance of gut microbiota. The fermentation process produces probiotics, organic acids, and other bioactive compounds that play an important role in strengthening the body's defenses and modulating the immune response through the gut-immune axis. In addition, the natural antioxidant content of fermented coffee can reduce oxidative stress and support digestive tract health. Literature studies show that consuming kombucha coffee has the potential to increase the population of beneficial bacteria in the intestine, inhibit pathogens, and improve the integrity of the intestinal barrier. These findings indicate that kombucha coffee has great prospects as an alternative functional beverage that supports holistic health. Further studies are needed to understand the specific biological mechanisms and standardization of production to ensure the safety and consistency of its benefits.Keywords: kombucha coffee, immune system, gut microbiota, fermentation, antioxidants